Activation of human mast cells through the platelet-activating factor receptor - Kajiwara, Naoki; Sasaki, Tomomi; Bradding, Peter; Cruse, Glenn; Sagara, Hironori; Ohmori, Kazumitsu; Saito, Hirohisa; Ra, Chisei; Okayama, Yoshimichi (Journal of allergy and clinical immunology, 2010)
In human subjects platelet-activating factor (PAF) concentrations are markedly increased in the plasma after anaphylactic reactions, and these correlate strongly with the severity of the response. The mechanism for the systemic spread of mast cell (MC) activation in anaphylaxis is often assumed to relate to the hematogenous spread of allergen, but this is implausible, and amplification mechanisms need to be considered. We have investigated the ability of PAF to induce human MC degranulation using skin, lung, and peripheral blood (PB)–derived cultured MCs and the signaling pathways activated in PB-derived MCs in response to PAF. The expression of PAF receptor was investigated by means of RT-PCR and Western blot analysis. Cell-signaling pathways in PB-derived MCs in response to PAF were investigated by analyzing the effect of various inhibitors and the silencing of phospholipase C (PLC) mRNA on PAF-mediated histamine release. We show for the first time that PAF induces histamine release from human lung MCs and PB-derived MCs but not skin MCs. Activation of PAF receptor–coupled G αi leads to degranulation through PLCγ1 and PLCβ2 activation in human MCs. PAF-induced degranulation was rapid, being maximal at 5 seconds, and was partially dependent on extracellular Ca 2+. Our findings provide a mechanism whereby PAF mediates an amplification loop for MC activation in the generation of anaphylaxis.